PENINGKATAN HASIL BELAJAR PKN, PEMAHAMAN NILAI-NILAI PANCASILA MELALUI METODE COOPERATIVE LEARNING PADA SISWA KELAS III SEKOLAH DASAR - Aisya Aisya; Reski Dewi Astika; Nurfadillah; Muanzir; Sulfasyah; Haris (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the results of student learning through the cooperative learning method in class III students of UPT SD Negeri 76 Tarowang Chapter 2 Civics Module. The purpose of this study is to determine the improvement in student learning outcomes in the subject of Civics on the material of Pancasila values through the cooperative learning method in class III students of UPT SD Negeri 76 Tarowang. In this study, the researcher used the Classroom Action Research (CAR) method. Data collection was carried out using student learning outcome tests and non-tests in the form of observation results using the cooperative learning method. First, the research in cycle 1 with an average of 650 or in other words, student learning outcomes have not reached the KKM. While in cycle II with an average of 980 or included in the complete category. The conclusion of this study is, student motivation and learning outcomes have increased after the implementation of the use of the cooperative learning method